2020
DOI: 10.1155/2020/3271975
|View full text |Cite
|
Sign up to set email alerts
|

The Ground-State Calculations for Some Nuclei by Mesonic Potential of Nucleon-Nucleon Interaction

Abstract: The interaction of Nucleon-Nucleon (N N ) has certain physical characteristics, which indicated by nucleon, and meson degrees of freedom. The main purpose of this work is calculating the ground state energies of 2 1 H and 4 2 He through the two-body system with the exchange of mesons (π, σ, ω) that mediated between two nucleons. This paper investigates NN interaction based on the quasirelativistic decoupled Dirac equation and self-consistent Hartree-Fock formulation. We construct one-boson exchange potential (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The start of using the fact that there is no unique potential for determination of the effective NN potential leads to exist different forms with different methods. So, this work concerned to show the effect of our potential which is published in previous work [1]. Our potential is constructed with the idea of one-boson exchange and also depends on the motion of nucleons in the nucleus.…”
Section: Theory Of Nn Through the Obepmentioning
confidence: 99%
“…The start of using the fact that there is no unique potential for determination of the effective NN potential leads to exist different forms with different methods. So, this work concerned to show the effect of our potential which is published in previous work [1]. Our potential is constructed with the idea of one-boson exchange and also depends on the motion of nucleons in the nucleus.…”
Section: Theory Of Nn Through the Obepmentioning
confidence: 99%
“…After long treatment of this potential as described in a previous study [23], we concluded our realistic optical potential, using the One-Boson-Exchange (OBE) model, as follows: The scalar and the vector parts of single meson exchange potential are defined in earlier studies [24][25][26][27]…”
Section: Theoretical Schemementioning
confidence: 99%
“…where the parameter To represent the static meson function, the suggested parameters by the Julich group [5] are presented in Table ( [19,27], so the bra wave functions collected by using Clebsch-Gordon and Talmi-Moshinsky-Smirnov (GTMS) coefficients [23,[29][30][31], then the bra is defined by:…”
Section: Theoretical Schemementioning
confidence: 99%
“…The interaction between a proton and a neutron with all other nucleons generates an average potential field where each nucleon moves. The interacted nucleons have a nuclear mean-field potential that depends on the position coordinates [15]. There is a capability to calculate the mean-field potential in nuclei.…”
Section: Introductionmentioning
confidence: 99%